Economic Benefits of Material Standardization: Average Annual Total Cost of Stock Material Item - Valonen, Annastiina (My University, 2019)
The emphasis of this thesis is to discuss the effects of material standardization in relation to the total cost formation of a material item. The primary objective is to analyse the cost structure and the price creating factors of stock material items in the case company context. After identifying the cost elements in the different life cycle phases, the organization can focus on improving the cost efficiency of the material process by eliminating the non-value adding activities. Furthermore, standardization aims to reduce the overlapping of similar material functions thus, the overall material process will enhance through the diminished item variety. The significance of the hidden and indirect costs is indicated and the impact of a wide material selection is reviewed in terms of cost. The thesis provides a literature review of the main research findings related to the subject as well as an observation of the case study context. Qualitative research methodology and a deductive approach are applied. The data is collected with semi-structured interviews of the main operators in the stock material process in the case organization. Additionally, data is gathered from several organization software. The obtained data is analysed according to content analysis principles and united by conclusive means. Moreover, the data is presented thoroughly to achieve a comprehensive outcome and to support the findings of the thesis. The main findings of the thesis are an estimation of the annual total cost of a stock material item as well as a blueprint tool for material total cost comparison. Furthermore, the study results demonstrates that additional costs form over a half of the total cost of a material item in relation to the purchasing price. The cost formation throughout the material process in the case situation is discussed and the main cost creating factors analysed. A prime observation is made of the non-value adding activities influencing the profitability and efficiency of the stock material process. Furthermore, the waste creating factors in terms of the stock material total cost are indicated and examined.
Keywords: material standardization; total cost of ownership; cost formation; manufacturing industry; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|